Svalbard Studies: Coal Mining in the Russo-Norwegian Context - Steinholt, Yngvar; Rogatchevski, Andrei (Poljarnyj vestnik, 2022)
This short article offers an introduction to Poljarnyj Vestnik’s special issue on Svalbard Studies.